2020
DOI: 10.1016/j.sjbs.2020.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal by ungulates in the point calimere wildlife sanctuary: A scientific and perspective analysis

Abstract: Exotic woody weed plants are a very serious threat to seed dispersed by ungulate in the tropical forest of Asia. The ungulates in Point Calimere Wildlife Sanctuary (PCWS) are a significant role in native indigenous seed dispersal. The exotic woody weed tree Prosopis juliflora prevalence distributed in the PCWS and they might potentially alter the native medicinal plant species. In the present investigation, we have assessed the seed dispersal by ungulates in PCWS from January to March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Blackbuck play important role in the seed dispersal of many medicinal plants growing in its habitat. Bulk of seeds dispersing by blackbuck through their digestive system, defecated seeds which fall on the ground and growing there naturally (Chandru et al 2020). Some of the earlier studies reported for the consumption and seed dispersal of P. juliflora in grassland habitat by Antilope cervicapra (Jadeja et al 2013;Corlett 2017;Yamato et al 2020).…”
Section: Economic Importancementioning
confidence: 97%
“…Blackbuck play important role in the seed dispersal of many medicinal plants growing in its habitat. Bulk of seeds dispersing by blackbuck through their digestive system, defecated seeds which fall on the ground and growing there naturally (Chandru et al 2020). Some of the earlier studies reported for the consumption and seed dispersal of P. juliflora in grassland habitat by Antilope cervicapra (Jadeja et al 2013;Corlett 2017;Yamato et al 2020).…”
Section: Economic Importancementioning
confidence: 97%
“…Locations close to natural forest will have a greater chance of getting the distribution of species compared to locations far away. Wind can aid species dispersal (Wan et al 2017;Nazareno et al 2021) by flying very small seeds and discarded wildlife (Chen et al 2017;Chandru et al 2020) through the poop. The distribution model determines the distance of seeds that animals can spread (Chen et al 2017).…”
Section: The Relations Of the Existence Of Natural Forest And Vegetat...mentioning
confidence: 99%
“…In addition, there is growing concern that where the trade in wild meat occurred, ungulates (including wild pig and deer) are important because it is profitable (Pangau-Adam et al 2012;Luskin et al 2014;Pattiselanno et al 2019;Pattiselanno et al 2020). Although, a study by Chandru et al (2020) indicates that ungulates play an important role in seed dispersal. Here, we aim to describe the hunting activities and identify hunted species and their conservation status to understand better the relationship between hunting prey and local livelihoods at the Bird's Head Peninsula (BHP) in Indonesian New Guinea and supposed to be projected on a wider dimension, including Asia and the Pacific.…”
Section: Introductionmentioning
confidence: 99%